Institutionalizing Kindness as a Systemic Value in Acehnese Madrasahs: A Bourdieusian Analysis of Religious Cultural Reconstruction - Lathifah Hanum; Nur Asma; Saidatul Khairiah; Winda Novianti (STAI Hubbulwathan Duri, 2025)
This qualitative case study investigated how Acehnese madrasahs systemically cultivate kindness (rahmah) through religious-cultural practices, bridging gaps between individual virtue ethics and institutional habituation in Islamic education. Data from observations, interviews, and document analysis across three madrasahs in Langsa, Aceh, reveal four key mechanisms: (1) the 5S framework (Senyum, Salam, Sapa, Sopan, Santun) routinizing empathetic interactions; (2) ritualized practices (e.g., congregational prayers, Quranic recitation) as moral rehearsals; (3) student-led community service fostering peer mentorship; and (4) Sharia-aligned policies embedding kindness in governance. These mechanisms form an embodied pedagogy where kindness transitions from abstract ideal to habitual behavior via repetition, teacher modeling, and cultural reinforcement. The study integrated Bourdieu’s habitus (embodied dispositions) and Lickona’s moral knowing-feeling-doing framework, demonstrating their synergy with Islamic epistemologies such as Sunnah-based rituals and maqasid al-shariah (objectives of divine law). While challenges like ritualism persist, reflective practices and peer accountability mitigate superficial compliance. The research offered a scalable model for institutionalizing kindness in Islamic education, emphasizing contextually rooted, policy-practice coherence. Thus, this study contributes to both theoretical discourse and practical application by demonstrating how culturally grounded, systemic approaches within Aceh’s Sharia-based context can effectively translate abstract ethical principles into tangible, lived expressions of virtue.